(untitled) (Comunicação & Inovação, 2023)
This study analyzed, under the light of French Discourse Analysis (DA), the description of the adjective ’military’, available in the 1980 and 2007 versions of Caldas Aulete. The delineation of the theoretical and methodological concepts of DA in the materialities shows that they are inserted in a pro-military and conservative ideological formation; and in an institutional discursive Formation in which the dictionary is the holder of the sayings. About the differences between the objects, the change in the setting of the examples stands out, regarding the conception of language and norm.